Modeling of Residential Environment Artistic Design Based on Multisensor Data Fusion - Yu, Yang (Wireless communications and mobile computing, 2022)
The development of a 3D city model is accompanied by the continuous progress of technical knowledge, the continuous increase of public interest in it, and the rapid progress of national knowledge. The use of a 3D city model has become the common concern of academia, enterprises, and most users. The article takes the community as an example to summarize the research overview and basic knowledge of the 3D model. From the aspects of 3D city location data collection technology, 3D city model technology, 3D exhibition, etc., the advanced technology in 3D city model, 3DGIS software system, and other issues are discussed and studied, and the current state-of-the-art technology development level is summarized and analyzed. The article first introduces the purpose and importance of the 3D town model and further analyzes the development context, research background, and research content at home and abroad. Secondly, the theoretical basis of the 3D data model, study location data characteristics, location data model configuration, location data survey structure, and location data model construction requirements were put forward. Then, 3DMax software was used to build a house model and finally find it in OpenGL software. The effective distance of the detector is 0.4~3.5 m, and the maximum resolution is 640×480. It also introduces the realization of 3D architectural model storage and the visual expression of 3D city modeling. The article uses the Kinect depth sensor to recreate a simple static dimensional scene.